The last Namsara - Ciccarelli, Kristen (HarperTeen, an imprint of HarperCollins Publishers, 2017)
In the beginning, there was the Namsara: the child of sky and spirit, who carried love and laughter wherever he went. But where there is light, there must be darkness -- and so there was also the Iskari. The child of blood and moonlight. The destroyer. The death-bringer. These are the legends that Asha, daughter of the king of Firgaard, has grown up learning in hushed whispers, drawn to the forbidden figures of the past. But it isn't until she becomes the fiercest, most feared dragon slayer in the land that she takes on the role of the next Iskari -- a lonely destiny that leaves her feeling more like a weapon than a girl. Asha conquers each dragon and brings its head to the king, but no kill can free her from the shackles that await at home: her betrothal to the cruel commandant, a man who holds the truth about her nature in his palm. When she's offered the chance to gain her freedom in exchange for the life of the most powerful dragon in Firgaard, she finds that there may be more truth to the ancient stories than she ever could have expected. With the help of a secret friend -- a slave boy from her betrothed's household --Asha must shed the layers of her Iskari bondage and open her heart to love, light, and a truth that has been kept from her